Analisis Pertumbuhan Laba pada Subsektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Purnawan, Amalina Firda; Suwaidi, Rahman Amrullah (Universitas muhammadiyah palembang, 2021)
Profit growth or profit owned by a company is how much profit they make this year compared to the previous year. This research use food and beverage sub-sector on the Indonesia Stock Exchange between 2017 and 2019 aims to analyze the effect of liquidity, leverage and activity on profit growth. Purposive sampling is the sampling method used in this study with the existing conditions and samples obtained from 15 food beverage sub-sectors. The use of multiple linear regression as a method of analysis and hypothesis testing is carried out on simultaneous (F) and partial (T) tests. The final result of this study is characterized by the absence of influence of the liquidity ratio and activity ratio on profit growth, while the leverage ratio has an influence on profit growth in the food and beverage subsector contained in the Indonesia Stock Exchange